A Case Study on Scheduling of Repairs in an Automobile Shop - Pilar, M. Fátima (2021)
The classical combinatorial problem of scheduling is extensively studied and arises in several economic domains. However, there are few studies in the automobile sector, particularly in scheduling vehicle repair tasks and using real instances. This paper intends to contribute to fill this gap, focusing on the scheduling of the repairs of the mechanical section of a Portuguese firm in the automobile sector. A mathematical model is presented that will assist the shop manager on the scheduling of the repairs, taking into account: the mechanics and other resources that are available, the mechanical interventions to be performed on each vehicle and its expected processing time. The aim is to reduce the time of inactivity of the vehicles between interventions, as well as, the downtime of mechanics, and therefore improve productivity. The results, from real instances extracted from the data provided by the firm, show that the interventions are scheduled in a suitable form, and there is a reduction of the downtimes.